LABOR GYMNASTICS: A PROPOSAL OF VALUATION OF THE LIFE IN THE WORK (Fiep Bulletin - online, 2014)
The article has as purpose to present the labor gymnastics offered to the servers and rendering of services of UnB/ The University of Brasilia, with the intention to improve the quality of life no work. The proposal of the Alive Project UnB, that had beginning in 1994, supported for the SRH/Human Resources Secretary and the DAC/Decanato de Assuntos Comunitários, has fomented action of social matrix well, in the human and professional growth. Worried about the physical and mental health of the involved ones, the labor gymnastics comes to contribute to minimize the levels of stress of the worker and to offer more quality to the labor tasks. The used methodology was evaluated by carried through questionnaire and interview with the servers who almost always worked seated in front of a computer. The instrument of initial inquiry, raised questions of integration, position and motivation that had been worked with intention to make possible modifications supported in acceptable ergonomic principles in the modern world. After the period of 12 months of execution of the labor gymnastics, perceived sensible improvement of the quality of life of the servers who had participated of the study, generating physical and mental benefits for the worker as well as for the institution.
Keywords: labor gymnastics; social integration; quality of life